2015
DOI: 10.1186/s12978-016-0120-5
|View full text |Cite
|
Sign up to set email alerts
|

Salient beliefs towards vaginal delivery in pregnant women: A qualitative study from Iran

Abstract: BackgroundChildbirth by cesarean section has increased at an alarming rate over the past few years in Iran. The present study was designed to explore pregnant women’s beliefs about the mode of delivery in order to provide some suggestions for future interventions to increase vaginal delivery.MethodsThis was a qualitative study framed by the Theory of Planned Behavior conducted in Tehran, Iran in 2013. Pregnant women attending public hospitals were recruited. The data were collected via in-depth interviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 30 publications
0
59
0
Order By: Relevance
“…In a cesarean section, there is usually a mother-baby withdrawal due to the limitations imposed by the surgery, so the care demanded by the baby cannot always be performed by the mother in the first hours or days of life, breastfeeding is delayed and may influence the desire of the woman to breastfeed. 16 It was observed in this study that although women prefer normal delivery over the cesarean section that, according to them, causes a long recovery and all the consequences that arise from this lack of mobility, knowledge about the way of delivery contradicts their expectations, because most when it comes to the way of delivery consider cesarean delivery as a quick fix and saves them from the anxiety of going through labor and the speed with which they can safely have their baby. Often the media transmits distorted information about childbirth, creating myths about some risky situations that would indicate caesarean sections.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a cesarean section, there is usually a mother-baby withdrawal due to the limitations imposed by the surgery, so the care demanded by the baby cannot always be performed by the mother in the first hours or days of life, breastfeeding is delayed and may influence the desire of the woman to breastfeed. 16 It was observed in this study that although women prefer normal delivery over the cesarean section that, according to them, causes a long recovery and all the consequences that arise from this lack of mobility, knowledge about the way of delivery contradicts their expectations, because most when it comes to the way of delivery consider cesarean delivery as a quick fix and saves them from the anxiety of going through labor and the speed with which they can safely have their baby. Often the media transmits distorted information about childbirth, creating myths about some risky situations that would indicate caesarean sections.…”
Section: Discussionmentioning
confidence: 84%
“…It is common for women who have undergone vaginal delivery to describe greater contentment, to present a more positive positioning of the delivery and to form a better bond with the baby. 16 In this sample, one of the women reported having had good prior experience with normal delivery, which is why I would like to repeat the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on reasons behind the high rate of CS in Iran (20)(21)(22)(23). Studies have shown that a main reason is willing of women to undergo CS due to fear of pain during labor and childbirth (21,24,25), concerns about genital modifications after vaginal delivery (26)(27)(28), belief that CS is safer for baby (29)(30)(31), and the convenience for women and their families (18). Studies show that women can play a major role in decision-making process about their birth (32)(33)(34)(35)(36).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…2,3 It is essential that health care providers provide continuous support to the mother during childbirth to enable her to have a natural delivery. 4 Tertiary referral centers have obstetric admissions with numerous obstetric and medical complications. 5 We sought to find out the outcome of mother and baby and background features among women delivering vaginally, in a referral centre where more women with complications are admitted for safe confinement.…”
mentioning
confidence: 99%